Isoquinoline Alkaloids and Indole Alkaloids Attenuate Aortic Atherosclerosis in Apolipoprotein E Deficient Mice: A Systematic Review and Meta-Analysis - Zhang, Yibing; Li, Min; Li, Xiangjun; Zhang, Tong; Qin, Meng; Ren, Liqun (Frontiers in Pharmacology, 2018)
Background: Several studies have attempted to relate the bioactive alkaloid with atherosclerotic cardiovascular diseases prevention in animal models, providing inconsistent results. Moreover, the direct anti-atherosclerotic effects of alkaloid have hardly been studied in patients. Therefore, the aim of this systematic review was to assess the reported effects of alkaloids on aortic atherosclerosis in ApoE-/- mouse models. Methods: Pubmed and Embase were searched to identify studies which estimated the effect of isolated alkaloids on atherosclerosis in apolipoprotein E deficient mice. Study quality was assessed using SYRCLE's risk of bias tool. We conducted a meta-analysis across fourteen studies using a random-effect model to determine the overall effect of the alkaloids, and performed subgroup analyses to compare the effects of the isoquinolone alkaloids and indole alkaloids. Results: The quality of the included studies was low in the majority of included studies. We clarified that alkaloid administration was significantly associated with reduced aortic atherosclerotic lesion area (SMD -3.19, 95% CI -3.88, -2.51). It is important to remark that the experimental characteristics of studies were quite diverse, and the methodological variability could also contribute to heterogeneity. Subgroup analyses suggested that the isoquinoline alkaloids (SMD -4.19, 95% CI -5.18, -3.20), and the indole alkaloids (SMD -2.73, 95% CI -3.56, -1.90) obviously decreased atherosclerotic burden. Conclusion: Isoquinoline alkaloids and indole alkaloids appear to have a direct anti-atherosclerotic effect in ApoE-/- mice. Besides the limitations of animal modal studies, this systematic review could provide an important reference for future preclinical animal trials of good quality and clinical development.